Analyzing of researches on gifted in science education in Turkey from 2018 to 2020 - YILDIRIM, MEHTAP (My University, 2022)
Purpose: This research aims at analyzing graduate theses and articles made on gifted individual in science education in Turkey through content analysis. Design/Methodology/Approach: In the research, 16 theses (10 master’s and six PhD theses) and 37 articles made between January 2018 and July 2020 were analyzed with content analysis. The studies were accessed from The Council of Higher Education National Thesis Center and Google Academic database. Findings: In the studies in which content analysis made, current issues were determined as STEM education, curriculum studies, and teaching material development. In most of the studies, qualitative research method was used and “case study” among qualitative research and “survey” among quantitative research models were frequently used. A limited number of experimental researches have shown that learning approaches such as STEM Education, Brain Based Learning, Differentiated Teaching, Argumentation Based Learning, Project Based Learning, Computer Based Learning have positive results on self-regulated learning strategies, attitude towards science, scientific process skills, problem solving skills, creativity and critical thinking skills. Highlights: It has been concluded that more experimental studies with different variables are needed on science education in gifted. Making studies on entrepreneurial skills, use of technology and different education levels are recommended.

Çalışmanın amacı: Bu araştırma, Türkiye’de özel yeteneklilerde fen bilimleri eğitimi üzerine yapılan lisansüstü tezlerin ve makalelerin incelenmesi amaçlamaktadır. Materyal ve Yöntem: Araştırmada, 2018 Ocak ayından 2020 yılı Temmuz ayına kadar yapılmış 16 tez çalışması (10 yüksek lisans ve altı doktora tezi) ve 37 makale içerik analizi ile analiz edilmiştir. Çalışmalara YÖK Ulusal Tez Merkezi ve Google Akademik veri tabanından ulaşılmıştır. Bulgular: İçerik analizi yapılan çalışmalarda güncel konular; STEM eğitimi, öğretim materyali geliştirme ve müfredat çalışmaları olarak tespit edilmiştir. Yapılan çalışmaların çoğunda nitel araştırma yöntemi kullanılmış ve nitel araştırma türlerinden “durum çalışması”, nicel araştırma türlerinden “tarama” modeli sık kullanılan modeller olmuştur. Sınırlı sayıdaki deneysel çalışmalarda; STEM Eğitimi, Beyin Temelli Öğrenme, Farklılaştırılmış Öğretim, Argümantasyon Tabanlı Öğrenme, Proje Tabanlı Öğrenme, Bilgisayar Destekli Öğrenme gibi öğrenme yaklaşımlarının öz düzenleyici öğrenme stratejileri, fene yönelik tutum, bilimsel süreç becerileri, problem çözme becerileri, yaratıcılık ve eleştirel düşünme becerileri üzerinde olumlu sonuçları olduğu görülmüştür. Önemli Vurgular: Özel yeteneklilerde fen bilimleri eğitimi üzerine farklı değişkenlerle daha fazla deneysel çalışma yapılmasına ihtiyaç olduğu sonucuna ulaşılmıştır. Özel yeteneklilerde girişimcilik becerileri, teknoloji kullanımı ve farklı öğretim seviyeleri ile ilgili çalışmalar yapılması önerilmektedir.
2018-2020 yılları arasında Türkiye'de özel yeteneklilerde fen eğitimi alanında yapılan çalışmaların incelenmesi
Keywords: Science education; Gifted; Content analysis; Fen bilimleri eğitimi; Özel yetenekli; İçerik analizi